The Implementation of a Pocket Book as a Family-Based Early Intervention Guide for Children with Autism - Herlina Yuni Setyowati; Jihan Rahma Indah Puspa Sari; Rifqi Farabi Al-Faruq; Fatma Avia Sholehah (Universitas Negeri Surabaya, 2026)
Early intervention plays an important role in supporting the development of children with Autism Spectrum Disorder (ASD), especially through active family involvement. However, parents' limited understanding of the characteristics of autism and early support measures remains a challenge. This study aims to explore parents' needs and describe the development and implementation of a pocket guide on early intervention for children with autism as a family-based guide. The study uses a qualitative approach with data collection techniques including in-depth interviews, observations, and documentation studies of parents of children with suspected autism and related practitioners. The developed pocketbook contains the characteristics of autistic children in terms of communication, social interaction, behaviour, and sensory aspects, presented in a simple and easy-to-understand manner. The pocketbook was developed based on a family-centred practice approach that places parents as key partners in the early intervention process. In addition, the pocket book is equipped with practical guidelines for parents when their children are suspected of having autism, including behavioural observation steps, early stimulation strategies at home, and directions for accessing professional services. The results of the study show that this pocket book helps improve parents' understanding, readiness, and involvement in the early support of children with autism.